Ibn Khaldun: Scientific Instruction as Prolonging the Polity - Shareef, Umar (İbn Haldun Çalışmaları Dergisi, 2018)
At a time when various forces threaten the continued life of democracy, Ibn Khaldun’s writings on education offer renewed importance to building longer lasting political regimes. In this paper, I argue that Ibn Khaldun views education as a crucial element for prolonging the polity and postponing the inevitable fall of dynasties. In the first part of the paper, I open with a discussion that situates his views within three broad debates in the literature: the first on Ibn Khaldun’s Muqaddima’s normative or descriptive nature; the second on its pessimistic or optimistic vision of human history; and the third on the role of statecraft. The second part of the paper identifies education as a crucial element for realizing the state’s ultimate objective: securing the context necessary for achieving human perfection. It also shows how scientific instruction strengthens the political well-being of the state by educating future leaders as well as perfecting the intellectual and moral character of the polity. I conclude with a discussion of the ideal instructor and Ibn Khaldun’s proposed teaching pedagogy. My paper has the potential to bring together Islamic and Western political thought and expands the political options available to Muslims within their own intellectual tradition. Ultimately, I contribute to the de-parochialization of western-dominated political theory by seriously contextualizing Ibn Khaldun within the Islamic tradition.